2006
DOI: 10.1111/j.1095-8649.2006.01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding behaviour and distribution of the tucunaréCichla aff. monoculus in a clear water river of the Bolivian Amazon

Abstract: The breeding behaviour and distribution of tucunare´Cichla aff. monoculus were studied for 2 months during the breeding season in the Paragua´River, Bolivia. Tucunare´were more abundant in the old remnant channels and isolated lakes than in the main river channel. The breeding period was delayed for c. 1 month in the river compared to the old remnant channels and lakes. The batch fecundity ranged between 3712 and 10 355 for females weighing 460 and 1380 g, respectively. Gonad analysis of egg-guarding or juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
5
24
0
1
Order By: Relevance
“…The decrease in the abundance of these species over the course of the study seems to be related to the trophic depression period of the ecosystem. Our results are also in agreement with other studies of introduced species that established successfully in many reservoirs in Brazil (Santos, Rocha, & Frédou, 2010;Chellappa et al, 2003;Santos, Silva, & Viana, 2003;Novaes et al, 2004; Bennemann, Carpa, Galvez, & Shibatta, 2006;Gomes, Dias, & Branco, 2008;Stefani & Rocha, 2009) and other countries (Japsen et al, 1997;Muñoz et al, 2006). Introduced species are extremely difficult to eradicate (Britton & Orsi, 2012), but a proposal to manage and control them is necessary to minimize their potentially harmful effects on the local aquatic community.…”
supporting
confidence: 82%
“…The decrease in the abundance of these species over the course of the study seems to be related to the trophic depression period of the ecosystem. Our results are also in agreement with other studies of introduced species that established successfully in many reservoirs in Brazil (Santos, Rocha, & Frédou, 2010;Chellappa et al, 2003;Santos, Silva, & Viana, 2003;Novaes et al, 2004; Bennemann, Carpa, Galvez, & Shibatta, 2006;Gomes, Dias, & Branco, 2008;Stefani & Rocha, 2009) and other countries (Japsen et al, 1997;Muñoz et al, 2006). Introduced species are extremely difficult to eradicate (Britton & Orsi, 2012), but a proposal to manage and control them is necessary to minimize their potentially harmful effects on the local aquatic community.…”
supporting
confidence: 82%
“…The size of male T. piresi at first maturity was greater than that of the females, an unusual pattern in tropical fishes, although larger males at first maturity are often observed in some cichlid species (Camara et al, 2002;Souza et al, 2008) because their reproductive behaviour, such as competition for spawning, parental care, and mate choice, is based mainly on criteria of size and colour (Lowe McConnell, 1969;Muñoz et al, 2006). Given this, the larger size of the T. piresi males may be related to reproductive strategies such as mate choice and spawning site selection.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern may be associated with environmental triggers (e.g., photoperiod, small variations in temperature and water transparency), or even residual behavior (endogenous factors) related to reproduction in natural conditions, i.e. Cichla usually reproduces during low water periods under a natural fluvial regime (Jepsen et al, 1999;Muñoz et al, 2006). In Venezuela, Jepsen et al (1997Jepsen et al ( , 1999 found trade offs between body condition and reproduction, demonstrating that Cichla species experience clear temporal variation in energy use via synchronized development of gonads, spawning, parental care (building and protection of nests) and growing.…”
Section: Discussionmentioning
confidence: 99%
“…Cichla species usually demand hydrological stability (i.e. low water level variation) and shallow areas to build nests and protect their fry (Winemiller, 2001;Muñoz et al, 2006), so Lajeado reservoir must offer adequate breeding conditions for C. piquiti. In addition, the regional climate in the Tocantins basin is tropical warm, so temperature is not a limiting factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation